Design of hybrid patch/slot antenna operating in induced "TM120 mode" - Tang, Ming-Chun (2013)
An ultralow-profile antenna based on a typical magnetic metamaterial unit cell, i.e., complementary electric resonator (CELC) structure, is introduced in this paper. The antenna behaves with an attractive performance of operating in induced “TM120 mode” as the fundamental resonance mode, which is much lower than TM100 mode. Compared to the reported miniature microstrip antennas based on slotting patch/ground technologies, the proposed antenna shows advantages in terms of low profile, high radiation efficiency, and low cross polarization. According to our investigation, even though the relatively strong backward radiation is accessorily caused due to the inherent complementary meander line (CML) slotting as a drawback for this type antenna, the peak gain in the broadside is much higher than a slot antenna with approximately the same dimensions.